Sheila Sweetinburgh, ed., Negotiating the political in Northern European urban society - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2016)
However, if ‘the Global Atlantic’experienced a ‘decline’in the late eighteenth and early nineteenth centuries there are some questions worth asking. Was the world, by the nineteenth century, less ‘Global’and more ‘Western’? Is it possible that the ‘Atlantic world’was less so after ‘the decline of the Global Atlantic’? How does the author’s conceptualization of sets of interactions ostensibly different between the early modern and the modern world, differ from other historiographical approaches to this transition?These questions are possible because Strobel takes the extra step of writing beyond the purely synthetic approach. Even when the book is an approachable, clear and concise synthesis, the author introduces thought-provoking concepts to his narrative. Strobel is successful in showing a world of multiple vectors simultaneously acting to shape the early modern world. The question remains whether any of the …